A Simple Modified Technique of Pleuropericardial Window: Towards 0% Recurrence - Hemead,Hanan M. (2022)
ABSTRACT Recurrent pericardial effusion is commonly encountered in neoplastic and infective disorders. Intervention is compulsory in patients with unstable hemodynamics and tamponading effusion. Surgical options include: pericardiocentesis, subxiphoid pericardiostomy, and pericardial window. The latter has proved to have lower incidence of recurrence; however, the technique has been continuously refined to improve the recurrence-free survival and decrease postoperative morbidity. We herein present a novel simple modification to minimize recurrence by anchoring the free edges of pericardial fenestration overlying the superior vena cava and right atrium to the chest wall. Follow-up showed no recurrence compared to 3.5% in the conventional procedure.